Anomalous Pressure Dependence of the Charge Density Wave and Fermi Surface Reconstruction in BaFe2Al9 - Mahmoud Abdel-Hafiez (1655398) (2025)
We investigate the pressure evolution of charge density wave (CDW) order in the intermetallic compound BaFe2Al9, which undergoes a pronounced first-order CDW transition ∼1 1 2 K at ambient pressure. High-pressure electrical resistivity and magnetization measurements reveal a systematic enhancement of the CDW transition temperature (TCDW) at a rate of ∼60 K / GPa, reaching 300 K under ∼3.2 GPa. The transition sharpness diminishes with pressure, indicating a crossover from first- to second-order behavior. Fermi liquid (FL) fits to the low-temperature resistivity reveal an increase in residual resistivity and a nonmonotonic evolution of the FL coefficient, indicating a pressure-induced Fermi surface (FS) reconstruction. Synchrotron x-ray diffraction reveals anisotropic lattice compression, a change in the compression trend of lattice parameters, and an abrupt change in microstrain at ∼3.6 GPa. Density functional theory calculations reveal pressure-induced flattening of quasi-two-dimensional FS sheets associated with the CDW nesting vector, consistent with enhanced nesting. These findings highlight the critical role of lattice strain and electronic structure evolution in stabilizing a high-temperature CDW phase, making BaFe2Al9 a rare example of a three-dimensional material where pressure promotes rather than suppresses the CDW order. Other Information Published in: Physical Review Letters License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1103/dxzf-fx8k